Pengelolaan Keuangan Melalui Literasi Keuangan Rumah Tangga Petani Desa Sarigadung - Sri Nani Youlanda; Diana Nurfida; Redhana Aulia; Putri Iftida'ul; Rahmawati; Bima Syarif Hidayatullah; Elvira Irmayana (Jurnal Inovasi Pengabdian Masyarakat, 2025)
Low financial literacy in Sarigadung Village is caused by unstructured and simplistic household bookkeeping. This community service program conducted financial management socialization and mentoring in collaboration with PKH facilitators for 30 farmer households over four weeks. The activities included counseling, mentoring, and distributing financial record booklets. Evaluation was carried out through interviews and income–expenditure evaluation sheets. Results showed that 80% of participants were able to record finances independently, and 75% expressed satisfaction with the activities. This program successfully improved community financial literacy and supported the economic stability of farming households in Sarigadung Village